The Role of Driver Services and Application Quality in Enhancing Gojek Customer Loyalty Through Satisfaction - Mutiarachim, Atika; Yuniarti, Nur Atika (SIMAK, 2024)
The purpose of this research is to determine the influence of Driver Services and Application Quality on Customer Loyalty through Customer Satisfaction, both directly and indirectly. Primary data was obtained through a Google Form questionnaire, the link of which was distributed online to Gojek customers throughout Indonesia resulting 120 respondents. Four data contained missing value and outliers so 116 data were used. Data was processed using Smart PLS 4.0. This research propose seven hypotheses. The results show five hypotheses can be accepted, however hypothesis of Application Quality on Customer Loyalty and Driver Services on Customer Loyalty through Customer Satisfaction obtained p-value > 0.05 so concludes to not influential.